Determination of Online Training in Increasing Productivity for Sustainable SMEs in Southwest Papua Province - Winarsih Winarsih; Darmawati Syam; Christoffel M.O. Mintardjo; Genita Gracia Lumintang (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the determinants of online training in increasing productivity and its impact on the sustainability of Small and Medium Enterprises (SMEs) in Southwest Papua Province. The focus of the study is directed at the direct effect of online training on SME sustainability and the indirect effect through productivity as an intervening variable. The research method uses a quantitative approach with an explanatory design. The study population is SMEs in Southwest Papua Province, who have participated in online training. The research sample was determined by purposive sampling, totaling 100 respondents. The research instrument was a questionnaire with a Likert scale that was tested for validity and reliability. Data analysis was conducted using Structural Equation Modeling (SEM-PLS) to examine the relationship between variables and the mediating role of productivity. The results show that online training has a significant positive effect on SME sustainability. Online training also has a significant effect on increasing productivity, and productivity has been shown to have a positive effect on SME sustainability. In addition, productivity plays a role as a partial mediating variable in the relationship between online training and SME sustainability. These findings confirm that online training will be more effective if the learning outcomes are implemented in increasing productivity, thereby strengthening the sustainability of SMEs in areas with limited infrastructure such as Sorong City.